An Ontological Analysis of Space Policy and Law: India's Space Activities Bill of 2017. Issue 3 (1st September 2020) - Anilkumar, Munikrishnappa; Ramaprasad, Arkalgud; Singai, Chetan; Sreeganga, S. D.
ABSTRACT: The Indian Space Activities Bill of 2017 (SAB 2017) seeks to promote exploration and growth of space activities in India. The Government of India solicited feedback on SAB 2017 from stakeholders and the public. As it is yet to become law, there is a need to examine SAB 2017 to better understand its proposed pathways to promote space activities effectively. For this purpose, a comprehensive ontological framework of space policy and law based on the extant research and policy literature on the topic is presented. It is a systemic framework, which helps in identifying gaps and recommending pathways for regulating space activities. In this article, the application of an ontological framework is put forward by assessing SAB 2017. The SAB 2017 is assessed by mapping its 31 sections onto the ontology and analyzing the data to highlight the bill's emphases on the elements, dimensions, and themes encapsulated in the ontology. Lastly, recommendations to bridge the gaps in SAB 2017 for promoting an effective and systematic growth of India's space activities are advanced.